What do bank acquirers want? Evidence from worldwide bank M&A targets - Caiazza, Stefano; Clare, Andrew; Pozzolo, Alberto Franco (Journal of Banking & Finance, 2012)
What drives bankers to create larger and larger, often multinational banking groups? In this paper we investigate whether the targets in cross-border bank M&As are materially different from those banks targeted in domestic M&A deals. The main message of this paper is that, with few exceptions, domestic and foreign investors target similar banks. In particular, and contrary to what one might expect, bank size does not have a different effect on the probability of being a domestic or a cross-border target, instead it has a positive and highly significant effect in both cases. We find that the main differences between national and international M&As are the characteristics of the countries where the banks operate.